2014
DOI: 10.1371/journal.pone.0111648
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of a Camembert-Type Cheese Using Freeze-Dried Tibetan Kefir Coculture as Starter Culture by Culture-Dependent and Culture-Independent Methods

Abstract: The biochemical changes occurring during cheese ripening are directly and indirectly dependent on the microbial associations of starter cultures. Freeze-dried Tibetan kefir coculture was used as a starter culture in the Camembert-type cheese production for the first time. Therefore, it's necessary to elucidate the stability, organization and identification of the dominant microbiota presented in the cheese. Bacteria and yeasts were subjected to culture-dependent on selective media and culture-independent polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
1
13
0
2
Order By: Relevance
“…As, it can grow in high salt concentrations (Aponte et al, 2010;Karasu-Yalcin et al, 2017;Padilla et al, 2014). Similar to our results, Mei et al (2014) found that K. servazzii was the dominant species along with S. cerevisiae in a Camembert-type cheese type by cultureindependent PCR-denaturating gel electrophoresis (PCR-DGGE). However, Lavoie et al (2012) reported that K. servazzii could be found in non-dominant microflora of milk and cheese along with P. membranifaciens.…”
Section: Results and Discussion Identification Of The Strains And Phylogenetic Analysessupporting
confidence: 88%
“…As, it can grow in high salt concentrations (Aponte et al, 2010;Karasu-Yalcin et al, 2017;Padilla et al, 2014). Similar to our results, Mei et al (2014) found that K. servazzii was the dominant species along with S. cerevisiae in a Camembert-type cheese type by cultureindependent PCR-denaturating gel electrophoresis (PCR-DGGE). However, Lavoie et al (2012) reported that K. servazzii could be found in non-dominant microflora of milk and cheese along with P. membranifaciens.…”
Section: Results and Discussion Identification Of The Strains And Phylogenetic Analysessupporting
confidence: 88%
“…The microbial community of TKGs constantly undergoes changes, which could mainly be attributed to different sub-culturing conditions. To date, based on various culture-dependent and culture-independent methods, approximately 15 bacterial species have been identified in TKGs collected from different Chinese regions, with most of them belonging to the Lactobacillus family ( Gao et al., 2012 ; Huang et al., 2013 ; Mei et al., 2014 ; Zheng et al., 2013 ; Zhou et al., 2009 ). In addition, other KGs also appear to comprise diverse bacterial species ( Nalbantoglu et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they are composed of mixed species of bacteria and eukaryotes, which are thought to be more stable than monospecies films (3,4). This behavior is also the case with microbial communities in food environments (5)(6)(7)(8)(9)(10). In the particular case of olive table fermentations, the presence of polymicrobial communities composed of yeasts and lactic acid bacteria (LAB) attached to both biotic (skin of the olives) and abiotic (inner fermenter walls) surfaces has been reported (11)(12)(13)(14).…”
mentioning
confidence: 95%